2019
DOI: 10.1002/hep.30846
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Minimum Acceptable Diagnostic Accuracy of Noninvasive Fibrosis Testing in Cirrhosis: A Decision Analytic Modeling Study

Abstract: No studies explore the clinical consequences of using noninvasive tests (NITs) compared to liver biopsy (LB) in diagnosing cirrhosis. Our aim was to combine two decision analytic models to determine the minimum diagnostic accuracy criteria for NITs to diagnose cirrhosis with equivalence to LB in terms of mortality. We further evaluated selected existing NITs used alone and sequentially. A decision tree was constructed with associated 2‐year mortality incorporating an LB or NIT strategy to diagnose cirrhosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Furthermore, direct biomarkers of fibrosis, such as ELF™ and PRO‐C3, have been demonstrated to be diagnostically superior to indirect indices such as APRI and FIB‐4 for the detection of advanced fibrosis . In a separate study, Majumdar et al concluded that APRI and FIB‐4 were unsuitable for the diagnosis of cirrhosis …”
Section: Direct Biomarkers Of Hepatic Fibrosismentioning
confidence: 99%
“…Furthermore, direct biomarkers of fibrosis, such as ELF™ and PRO‐C3, have been demonstrated to be diagnostically superior to indirect indices such as APRI and FIB‐4 for the detection of advanced fibrosis . In a separate study, Majumdar et al concluded that APRI and FIB‐4 were unsuitable for the diagnosis of cirrhosis …”
Section: Direct Biomarkers Of Hepatic Fibrosismentioning
confidence: 99%
“…Patients in whom the second line of tests confirms advanced fibrosis should be referred to a hepatologist in order to reliably assess the presence of cirrhosis and portal hypertension, as these require further specific investigations that include screening for the presence of oesophageal varices and HCC [73]. Since noninvasive tests have a modest positive predictive value for cirrhosis (about 50 to 70%), patients who have been diagnosed with cirrhosis based on noninvasive tests usually need a liver biopsy to reliably determine the stage of fibrosis, as well as to assess the presence of other histological components [8,74]. As explained in the previous paragraph, it may be useful to quantify steatosis at baseline and during the follow-up period, although solid scientific evidence is still lacking.…”
Section: How Should Liver Disease and Associated Extrahepaticmentioning
confidence: 99%
“…8 Several non-invasive methods are available for ruling out advanced fibrosis in ALD; however, a liver biopsy is still required to establish the diagnosis and assess the exact stage of disease in selected patients. 9,10 There is no histological scoring system developed specifically for ALD; however, liver fibrosis is routinely reported using the semiquantitative Brunt histological scoring system. 11 A recent study confirmed that advanced fibrosis is associated with liver-related mortality in patients with early/compensated ALD.…”
Section: Introduction Globally 24 Billion People Consume Alcoholmentioning
confidence: 99%